Consideraciones sobre el cálculo infinitesimal leibniziano y el cálculo de fluxiones newtoniano - Viñuela Villa, Pedro A. (2014)
This paper compares the Leibni- zian calculus and Newtonian calculus in order to present some relevant aspects of Leibniz’s thought: the importance of symbolism in mathe- matics, the relation between the doctrine of symbolic thought and the vision of infinitesimals as «useful fictions».